The Between Commitment and Implementation: Indonesia’s Response to ACTIP in Addressing Human Trafficking - Rachmania Dwi Septiana; Maulana Rifai; Prilla Marsingga (al-Afkar, Journal For Islamic Studies, 2026)
This study analyzes the implementation of the ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP) in Indonesia during 2017-2025, focusing on the gap between normative commitment and law enforcement practice. Although Indonesia ratified ACTIP through Law No. 12/2017 and possesses a comprehensive national legal framework, trafficking cases continue to increase from 340 cases (2017) to 798 cases (2023), indicating that compliance has not been substantively realized. This research employs a qualitative descriptive approach based on document analysis to identify factors hindering effective ACTIP implementation. Findings reveal that Indonesia's compliance remains normative with systematic obstacles across three pillars: weak prevention due to structural factors, ineffective victim protection due to policy-practice gaps, and suboptimal law enforcement due to limited capacity of local authorities, weak coordination, and differing interpretations of TIP elements. This study emphasizes the importance of strengthening institutional capacity and adopting victim-centered approaches to ensure regional commitments generate substantive impact.